2012
DOI: 10.1016/j.vetpar.2012.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the transmission of Haemonchus contortus

Abstract: Infection with the gastrointestinal nematode Haemonchus contortus causes considerable losses in the sheep industry. In this study, we evaluated the effect that climate has on third-stage larvae (L3) of H. contortus in terms of their migration from sheep feces to Brachiaria decumbens grass, as well as their distribution among the forage plants. Fecal samples containing H. contortus L3 was deposited on the soil among the herbage at an initial height of 30 cm. Sample collection began 24h after contamination and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 16 publications
4
29
1
3
Order By: Relevance
“…In spring, in both grasses, most larvae were recovered from the upper portions of the plants. Studying the survival and migration of Haemonchus contortus, Santos et al (2012) verified that during summer, there was no difference in larval recovery among the different strata analyzed (0-10, 10-20, and >20 cm). During autumn and winter, most L3 were recovered from the lower stratum (0-10 cm).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…In spring, in both grasses, most larvae were recovered from the upper portions of the plants. Studying the survival and migration of Haemonchus contortus, Santos et al (2012) verified that during summer, there was no difference in larval recovery among the different strata analyzed (0-10, 10-20, and >20 cm). During autumn and winter, most L3 were recovered from the lower stratum (0-10 cm).…”
Section: Introductionmentioning
confidence: 80%
“…These authors stated that temperatures below 16°C or above 36°C limit the development of Haemonchus and Trichostrongylus, the main nematodes found in the present study. Santos et al (2012) observed that precipitation favors L3 movement from feces to pasture and, despite high temperatures, can speed the movement of larvae to the tops of grass blades. These factors may explain the The variance analysis was carried out with the logarithmically transformed (log (y)) data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rainfall season the humidity increases 70-85%. For example for Haemonchus contortus high rainfall is related to a proportional increase of the number of migrated L3 from fecal material to pasture (Santos et al, 2012;Silva et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Hematophagus gastrointestinal nematodes cause emaciation, anemia and even death of infected animals, ultimately leading to substantial economic losses to the livestock production (Ghisi et al 2007). Among various helminthic infections of small ruminants, major threat and impediment to ruminant livestock farming occurs in the form of gastroenteritis caused by Haemonchus contortus (Santos et al 2012). McLeod (2004) approximated the annual treatment cost due to H. contortus to be around $103 m in India.…”
Section: Introductionmentioning
confidence: 99%